Total Quality Management dalam Pelayanan Pendidikan (Studi pada Dinas Pendidikan Kota Malang) Mukhammad Dliya’ Muzakka, Endah Setyowati, Trisnawati - Muzakka, Mukhammad Dliya (Jurnal Administrasi Publik, 2016)
Abstract: Total Quality Management in Educational Services (Case on Education Department of Malang City). The quality of education in Indonesia is still low, that’s caused by several things, such as: Pattern of education implementation, policy of education implementation, the teacher’s role and the community.Therefore, there should be efforts to improve the quality of education by using clearly and varied indicators, so that can know the condition of the education quality and educational services. The type of research used a descriptive study with qualitative approach and limited by a research focus, that is the quality of educational services is based on the characteristics in Total Quality Management, such as: Focus at customer, Obsession to quality, Scientivice approach, Long term commite, Cooperate team, Continuous improvement system, Education and training, Freedom which in control, Unity of target, Existence of involvement and enableness of officer. Keywords: Total Quality Management, educational, services